Optimasi Logistic Cost dari Perusahaan Crossdock Menggunakan Pendekatan Linear Programming dengan Permintaan Stokastik - Maryadi, Deri (Fakultas Teknik Universitas Tulang Bawang, 2025)
Efficiency within a company must be enhanced to maintain competitiveness and business sustainability, particularly in logistics firms. In logistics processes, minimizing costs is a critical indicator of operational efficiency. This study applies optimization through linear programming to a cross-dock company characterized by fluctuating demand, focusing on a fast-moving product. The analysis begins by calculating the minimum and maximum demand based on twice the standard deviation from the mean, followed by determining the optimal scenarios for each depot. The results indicate that, for the eight depots, the majority of the truck selection involved using single-axle trucks. Consequently, the total cost from the first to the seventh week was Rp. 1,785,000,000, while the LP simulation results indicated a total cost of Rp. 1,214,000,000, representing a potential cost saving of Rp. 554,000,000. Keywords: Cross-Dock, Linear Programming, Logistic Cost, Optimization